Women's Transformational Leadership In Improving Public Services: A Systematic Review - Rudiana, Rana; Nunung, Ai; Ratna H, Yunyun; Pujihartanti, Erna; Veranita, Mira (Asosiasi Ahli Administrasi Indonesia, 2025)
This study addresses the limited scholarship on the specific contribution of women’s transformational leadership in enhancing public service quality. While prior research often examines women’s leadership or transformational leadership separately, few systematically explore their intersection in the public sector. To bridge this gap, a systematic narrative review was conducted on 11 selected articles retrieved through Elicit AI. Thematic and contextual analysis was employed to identify patterns, themes, and theoretical constructs across organizational and sectoral contexts. Findings reveal that women leaders consistently demonstrate the four core dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These practices foster inclusive, ethical, and innovative organizational cultures aligned with the demands of modern public service. However, contextual challenges such as organizational culture, social norms, gender stereotypes, and limited access to strategic roles shape the effectiveness of women’s leadership. Theoretically, this study contributes to leadership and gender scholarship by integrating transformational leadership theory into the domain of public administration. It underscores the importance of empathetic, participatory, and visionary leadership in advancing sustainable service reforms. Overall, the synthesis highlights how empowering women in transformational leadership roles enhances public service effectiveness and drives bureaucratic change, while calling for further research on intersectionality and cross-sectoral dynamics.